Sneddon's syndrome: case report and review of its relationship with antiphospholipid syndrome - Dutra, Livia Almeida [UNIFESP] (2012)
The Sneddon's syndrome is a rare disorder characterized by the occurrence of cerebrovascular disease associated with livedo reticularis. The antiphospholipid syndrome is the most frequent type of acquired thrombophilia, defined by the occurrence of thrombosis or pregnancy morbidity in the presence of persistently positive antiphospholipid antibodies. Approximately 80% of Sneddon's syndrome patients have an antiphospholipid antibody marker. These antibodies may play a pathogenetic role in some cases of Sneddon's syndrome, and many authors consider these two syndromes as the same entity. Although clinical features of antiphospholipid syndrome and Sneddon's syndrome may overlap, there is a distinction between clinical and laboratory evidence suggesting that these two entities are different diseases. A recent finding of coagulopathies, including elevated levels of coagulation factor VII, decreased levels of protein S, and activated protein C in Sneddon's syndrome patients suggested a possible biological link between the vasculopathy and a primary coagulopathy. Moreover, the clinical course seems to be progressive in Sneddon's syndrome patients and includes increase of disability and cognitive deterioration, more arterial involvement, and the antiphospholipid syndrome shows a more benign course. Both syndromes share clinical and laboratory features, and whether Sneddon's syndrome represents a spectrum of antiphospholipid syndrome remains unclear. Sneddon's syndrome patients have a worse prognosis and may represent a subgroup of patients who demands more rigorous follow-up. It is important to recognize the Sneddon's syndrome, particularly because stroke episodes may be prevented through appropriate treatment.